2022
DOI: 10.3390/genes13101753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-1,6-Glucan Synthase Gene (FfGS6) Overexpression on Stress Response and Fruit Body Development in Flammulina filiformis

Abstract: β-1, 6-glucan synthase is a key enzyme of β-1, 6-glucan synthesis, which plays a vital role in the cell wall cross-linking of fungi. However, the role of the β-1, 6-glucan synthase gene in the development of the fruiting body and the stress response of macrofungi is largely unknown. In this study, four overexpression transformants of the β-1, 6-glucan synthase gene (FfGS6) were successfully obtained, and gene function was studied in Flammulina filiformis. The overexpression of FfGS6 can increase the width of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Besides the light and temperature, many cultivation substrates often bring oxidative stress and mechanical damage often occurs. During the growth of F. filiformis , we adopted the exogenous addition of H 2 O 2 (5 mM and 10 mM, according to Liu et al [ 20 ]) and MeJA (0.01 mM and 0.02 mM, according to Ren et al [ 21 ]) as two cases of environmental stress to detect the response expression of FfSpdsSr . The RT-qPCR results showed that FfSpdsSr significantly up-regulated under 10 mM H 2 O 2 treatment ( Figure 4 E) or under 0.01-0.02 mM MeJA treatment ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the light and temperature, many cultivation substrates often bring oxidative stress and mechanical damage often occurs. During the growth of F. filiformis , we adopted the exogenous addition of H 2 O 2 (5 mM and 10 mM, according to Liu et al [ 20 ]) and MeJA (0.01 mM and 0.02 mM, according to Ren et al [ 21 ]) as two cases of environmental stress to detect the response expression of FfSpdsSr . The RT-qPCR results showed that FfSpdsSr significantly up-regulated under 10 mM H 2 O 2 treatment ( Figure 4 E) or under 0.01-0.02 mM MeJA treatment ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…For the temperature treatment, four gradients—15 °C (cold stress), 20 °C (low-temperature stress), 25 °C (the optimum temperature, as control), and 30 °C (high-temperature stress)—were used to cultivate F. filiformis mycelia after inoculation on CYM plate, according to the study of Lv et al [ 19 ]. Because fungi are often subjected to oxidative stress from growing substrates and mechanical damage from the external environment, the exogenous H 2 O 2 (5 mM and 10 mM, according to Liu et al [ 20 ]) as the representative of oxidative stress and exogenous MeJA (0.01 mM and 0.02 mM, according to Ren et al [ 21 ]) as the representative of mechanical damage (due to the previous study that showed mechanical damage acts through JA signal [ 22 ]) were added into the CYM medium to cultivate F. filiformis mycelia. All samples were wrapped in foil, quick-frozen in liquid nitrogen, and stored in a −80 °C freezer for future use.…”
Section: Methodsmentioning
confidence: 99%